A handover technique for inter- and intra- domain proxy mobile IPv6 in vehicular network environment - Hussain, Haider N. (2013)
The provision of mobility is an essential feature of Vehicular Ad-hoc network (VANET) environments. In order to leverage mobility for wireless users, other researchers proposed an extension of MIPv6 which has been proven capable of supporting network mobility (NEMO). However, the Proxy Mobile IPv6 (PMIPv6) mobility protocol does not support seamless inter-domain vehicles handover and global mobility functionality. As a result, vehicles suffer from high handover latency and packet loss. Thus, there is a need to develop efficient inter-intra domain PMIPv6 techniques that consider the vehicular network environment for a seamless interdomain handover. This thesis introduces an enhancement of the PMIPv6 protocol based on Media Independent Handover (MIH) known as inter-domain PMIPv6 techniques that provide seamless inter-domain handover for vehicles. Next, a handover Estimation Engine (EE) is proposed to improve the handover process, followed by an intra-domain technique to support continuous connection for vehicles crossing inter-intra domains. A series of experiments to test handover latency, communication overhead, and packet loss were conducted using highway vehicular scenarios. The findings were compared with results from other inter-intra PMIPv6 schemes. The comparison showed that the proposed techniques reduced approximately 18% of the inter-domain and 27% of the intra-domain handover latency time besides supporting continuous connection. The proposed techniques have been proven to be capable of providing inter-domain connections to resolve the global mobility support problem.